Genetic polymorphisms in the prostaglandin pathway genes and risk of head and neck cancer. (28th April 2014) - Lee, W‐T; Huang, C‐C; Chen, K‐C; Wong, T‐Y; Ou, C‐Y; Tsai, S‐T; Yen, C‐J; Fang, S‐Y; Lo, H‐I; Wu, Y‐H; Hsueh, W‐T; Yang, M‐W; et al.
<x xml:space="preserve">Abstract</x> Objective Previous studies examining the association between genetic variations in prostaglandin pathway and risk of head and neck cancer (HNC) have only included polymorphisms in the PTGS2 (COX2) gene. This study investigated the association between genetic polymorphisms of six prostaglandin pathway genes (PGDS, PTGDS, PTGES, PTGIS, PTGS1 and PTGS2), and risk of HNC. Methods Interviews regarding the consumption of alcohol, betel quid, and cigarette were conducted with 222 HNC cases and 214 controls. Genotyping was performed for 48 tag and functional single‐nucleotide polymorphisms (SNPs). Results Two tag SNPs of PTGIS showed a significant association with HNC risk [rs522962: log‐additive odds ratio (OR) = 1.42, 95% confidence interval (CI): 1.01–1.99 and dominant OR = 1.58, 95% CI: 1.02–2.47; rs6125671: log‐additive OR = 1.49, 95% CI: 1.08–2.05 and dominant OR = 1.96, 95% CI: 1.16–3.32]. In addition, a region in PTGIS tagged by rs927068 and rs6019902 was significantly associated with risk of HNC (global P = 0.007). Finally, several SNPs interacted with betel quid and cigarette to influence the risk of HNC. Conclusions Genetic variations in prostaglandin pathway genes are associated with risk of HNC and may modify the relationship between use of betel quid or cigarette and development of HNC.